Parenting pada Single Parent (Ibu) yang Memiliki Anak Autis (Studi Kasus di Terapi Autis Cahaya Harapan Kelurahan Rejomulyo, Kecamatan Kota Kediri) - Agathista Eka Wulandari (PG-PAUD Trunojoyo, 2017)
The fruit of the heart is the desire of each parent, when have deficiencies in the baby in this stage of development and growth can not be maximized as experienced by children with autism at an early age. So the most important thing is the application of parenting. In this study wanted to see how the application of parenting in the mother who acts as a single parent who has children with autism. The subjects in the study are two subjects of Autism Therapy of Light Hope Rejomulyo Village, District Kedir District. The research method is a qualitative case study approach. The results obtained in this study can be concluded that single parent (mother) applying authoritative parenting with creative ways so that develop the competence of children with autism condition is done by providing formal education, informal, and nonformal to improve the ability of children with children with autism. So in getting the results that autistic children are cared for by using authoritative parenting tends to have socioemosional better than autistic children who cared for using parenting authoritarian, neglectful parenting, and indugent parenting